Socialization Of Safe And Wise Use of Drugs To The Community in Wonorejo Village - Agnes Prawistya Sari; Hanugrah Ardya CS; Agustina - Pujilestari; Sufiina Pinto L; Adhi Wardhana Amrullah; Rolando - Rahardjoputro; Joko - Santoso; Berliana - Lutfiananda; Anggi Putri Aria Gita (Universitas Malahayati Lampung, 2026)
ABSTRACT The inappropriate use of ethical drugs and antibiotics in self-medication practices remains a global health issue, posing risks of adverse effects and antimicrobial resistance. Low health literacy in the community, including in Wonorejo Village, underscores the need for education on rational drug use. This Community Service (PKM) activity aims to increase community knowledge and awareness regarding the safe, wise, and regulated use of medicines. The activity was conducted in 10 May 2025 in Ceplukan Hamlet, Wonorejo Village, targeting 42 members of the PKK. The educational methods employed included lectures, interactive discussions, and demonstrations using leaflets and drug samples. Effectiveness was evaluated by comparing pre-test and post-test scores.The implementation showed a significant increase in participants' understanding, with the average score rising from 71.4 to 87.6. The number of participants in the high-score range (90–100) increased from 5 to 18, with no participants scoring below 50 in the post-test. Community-based education is effective in improving pharmaceutical health literacy. This socialization encourages safe and responsible self-medication behavior as a preventive measure to maintain public health quality. Keywords: Antibiotics, DAGUSIBU, Ethical Drugs, Health Education, Self-medication.